KONSEP ADAB MENUNTUT ILMU DALAM KITAB WASHOYA KARYA SYAIKH MUHAMMAD SYAKIR DAN RELEVANSINYA DENGAN TUJUAN PENDIDIKAN ISLAM - Nurzaman, Jajang; Suhartono; Ikhsanudin, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of adab (ethics) in seeking knowledge, which has increasingly declined in modern education due to its pragmatic and materialistic orientation. The main problem of this research is to analyze the concept of adab in seeking knowledge according to Syaikh Muhammad Syakir in the book Washoya and its relevance to the goals of Islamic education. This study aims to (1) identify and analyze the concept of adab in seeking knowledge in the book Washoya, and (2) examine its relevance to the objectives of Islamic education as stated in Law Number 20 of 2003 concerning the National Education System. This research employs a qualitative descriptive approach with a library research method. The primary data sources include the book Washoya Al-Aba Lil Abna and Law Number 20 of 2003, while secondary data are obtained from books, journals, and related scientific works. Data collection is conducted through documentation, and data analysis uses content analysis techniques. The results of the study indicate that the concept of adab in seeking knowledge includes seriousness in learning, proper time management, engaging in discussions, respecting teachers, humility (tawadhu’), and reliance on Allah (tawakkal). Furthermore, the relevance between the concept of adab and the goals of Islamic education lies in their shared emphasis on character building, the pursuit of knowledge as a means to attain Allah’s pleasure, and the formation of individuals who are faithful, pious, knowledgeable, and morally upright in accordance with Islamic educational objectives.